2010
DOI: 10.1152/ajpgi.00169.2010
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine transport is mediated by both endocytic and solute carrier transport mechanisms in the gastrointestinal tract

Abstract: The polyamines spermidine and spermine, and their precursor putrescine, are required for cell growth and cellular functions. The high levels of tissue polyamines are implicated in carcinogenesis. The major sources of exogenous polyamines are diet and intestinal luminal bacteria in gastrointestinal (GI) tissues. Both endocytic and solute carrier-dependent mechanisms have been described for polyamine uptake. Knocking down of caveolin-1 protein increased polyamine uptake in colon cancer-derived HCT116 cells. Diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 22 publications
(19 reference statements)
1
70
0
2
Order By: Relevance
“…21 Estimated levels of extracellular PAs in plasma and inflamed tissues range from mM to mM. 33 Evidence for a functional role of extracellular PAs include: vesicular release of PAs by depolarization of brain slices, 4 transport of exogenous PAs from dietary intake and gut bacteria sources into gastrointestinal cells, 5 external block and activation of GluR channels, [25][26][27][28] activation of the TRPV1 capsaicin receptor channel in peripheral sensory neurons, 33 and gating shift of Ca V channel current.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Estimated levels of extracellular PAs in plasma and inflamed tissues range from mM to mM. 33 Evidence for a functional role of extracellular PAs include: vesicular release of PAs by depolarization of brain slices, 4 transport of exogenous PAs from dietary intake and gut bacteria sources into gastrointestinal cells, 5 external block and activation of GluR channels, [25][26][27][28] activation of the TRPV1 capsaicin receptor channel in peripheral sensory neurons, 33 and gating shift of Ca V channel current.…”
Section: Resultsmentioning
confidence: 99%
“…36 A prolonged 30 min exposure of transfected HEK293 cells to 1 mM extracellular spermidine or spermine suppresses the time course of recovery from inward rectification in the whole-cell mode (Fig. 5), suggesting that slow cellular uptake of PAs by endocytosis or transport proteins 5,6 may be a physiological mechanism of Na V channel modulation. The fact that cytoplasmic PAs block outward Na V current in a voltage-dependent manner 39 indicates that PAs are likely to bind within the Na + conduction pathway accessible from the intracellular side of the channel.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We observed a partial rebound in putrescine levels at 12 months, but levels remained approximately 50% below those found at baseline. Putrescine is the most prevalent dietary polyamine (44) and is the preferred substrate for the polyamine transport system (45). A study in patients with prior colorectal adenomas found that putrescine levels rebounded in normal rectal mucosa after 12 months of continuous low-dose DMFO (500 mg/d), suggesting an adaptive response to prolonged ODC suppression with a compensatory cellular uptake of diet-or bacteria-derived putrescine (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, the transport system for polyamines in bacteria through transporters is different from that of animals through endocytosis (Uemura et al 2010 ). Some bacteria and most animals use ornithine decarboxylase for polyamine biosynthesis.…”
Section: Studies On Pathogenic Bacteria and Polyamine Transportersmentioning
confidence: 99%